UKRAINIAN BORDER GUARDS INTEROPERABILITY ASSESSMENT IN THE FRAMEWORK OF COMMON EUROPEAN BORDER GUARD STANDARDS IMPLEMENTATION - Andrii Balendr; Oksana Komarnytska; Ihor Bloshchynskyi (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The paper reports on an innovative approach to evaluate the level of harmonisation of Ukrainian border guards training with the common standards for border guarding in the European Union (EU) member-states. There are different types of borders and different organisational structures in border guard agencies in the EU. The authors present the results of a research aimed at analysing the level of interoperability of Ukrainian border guards. In case of border guards' training, interoperability stands for their level of professional readiness for joint actions with representatives of foreign border guard authorities. For this purpose, the EU border guard agencies under the supervision of the European Border and Coast Guard Agency (Frontex Agency) introduced the Interoperability Assessment Program (IAP), as the means to assess, first of all, the level of integration of the Common Core Curriculum (CCC) for basic border guards' training into border guard authorities' national curricula. The programme's results provide information on the degree to which the CCC meets the requirements regarding its content. The overall CCC implementation at the NASBGSU was 77.5%, namely: by modules (General Studies - 95%; Land Border Module - 75%; Air Border Module - 81%; Sea Border Module - 58,6%); by content (General studies - 96%; Legislation - 73,9%; Practice - 80,8%). The results of the evaluation held at the National Academy of the State Border Guard Service of Ukraine named after Bohdan Khmelnytskyi, involving cadets of the Faculty of Foreign Languages and Humanities showed that Ukrainian border guards and their system of education and training are in line with the EU member-states' common standards and the Ukrainian border guard agency personnel can be effectively used for the various operational and service activities of protecting different border sectors.